An Iterative Method for Empirically-Based Q-Matrix Validation - Ragip Terzi; Jimmy De La Torre (International Journal of Assessment Tools in Education)
In cognitive diagnosis modeling, the attributesrequired for each item are specified in the Q-matrix. The traditional way ofconstructing a Q-matrix based on expert opinion is inherently subjective,consequently resulting in serious validity concerns. The current study proposesa new validation method under the deterministic inputs, noisy “and” gate (DINA)model to empirically validate attribute specifications in the Q-matrix. Inparticular, an iterative procedure with a modified version of the sequentialsearch algorithm is introduced. Simulation studies are conducted to compare theproposed method with existing parametric and nonparametric methods. Resultsshow that the new method outperforms the other methods across the board.Finally, the method is applied to real data using fraction-subtraction data.